Representações do léxico sertanista em corpus da Literatura regionalista brasileira: protótipo de vocabulário etnoterminológico online - Pimenta, Ana Paula Corrêa (2019)
Starting from an ethnoterminological perspective, an attempt to bring Linguistics and Literature together, we seek in this work to analyze the lexical units, in the quality of vocab-terms, used in the sertanista regionalist literary discourse, with the intention of proposing a vocabulary and of making it available on a webpage for students and literature teachers. Because it is a repertoire that brings meanings of the sertanista literary universe, we understand that our proposal of Vocabulary can serve as an aid to students and teachers of literature in the activities of reading and interpretation of the literary text and also to others interested in the study or ethnoterminological product, such as: literary critics, linguists, lexicographers, terminographers. To these ends, we started with a study corpus composed of twenty regionalist literary works of sertanista themes by notable authors in the Brazilian Literature, five of them coming from picturesque Regionalism, ten from Critical Regionalism and five from Super-Regionalism, forming a total of three subcorpora. The study corpus, when processed by the program WordSmith Tools 6.0, specifically by its three tools: Concord, KeyWords and WordList, allowed us to identify the vocab-terms and have access to their linguistic contexts of occurrences to elaborate the definitions proposals. Thus, we elaborate the ethnoterminographic fiches, constructed the vocabulary entries and described the microstructure and the macrostructure of the vocabulary, demonstrating at each stage the feasibility of our proposal. We conclude that the vocab-terms present semantic specificities referring to the socio-linguistic-cultural universe of the sertanejo, that they erect from the linguistic conceptualization of this group. These units acquire this double functionality (vocab and term) in the sertanista regionalist literary discourse due to the following aspects: they are part of a conceptual system structured within a specific theme, the sertanista theme; act in the composition of a fictional world semiotically constructed by the modeling force of literary language; have intertextuality and interdiscursivity intra and interuniverse of discourse with ethnoliterary discourses; they actualize a system of values, a system of beliefs, in short, the axiology of a specific group, the sertanejo of the Brazilian backlands; designate concepts formed with semes of the universe of discourse in which they are used; refer to the particularities of a real/fictional world as to its symbolic function; act on the memory plane, so that it is possible to retrieve from the narratives elements of the culture and language of the sertanejo, still present in our society. Thus, we believe that this work may result in significant contributions to ethnoterminological studies and, also, serve as subsidy for new ethnoterminographic works and future research.